Financial reforms and interest rate spreads in the commercial banking sector in Kenya - Munene, Daniel (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2006)
Financial reforms were a major component of structural adjustment programs deemed necessary for developing countries in the mid 1980s. These were not only meant to improve the sector, but would ultimately enhance economic growth and help in poverty alleviation. At the top of these reforms was financial liberalisation. Kenya, like many other sub-Saharan African countries, undertook financial liberalisation in 1991, one of the measures was decontrolling interest rates. With market driven interest rates in place it was assumed that there would be increased efficiency in bank lending, as well as growth in credit availability as deposits increased. A key indicator of this improved intermediation process would be a narrowing interest rates spread, that is, the margin between the deposit and lending rate. Paradoxically, however, the expected benefits of these reforms did not accrue to Kenya's banking sector. This study focuses on financial reforms and the spread of interest rates in Kenya's banking sector. Using a trend analysis, spanning the period before and after liberalisation, interest rates spread are shown to have escalated dramatically upwards after liberalisation. An analysis of three macroeconomic variables, namely, the exchange rate, inflation rate and economic growth offer little, or inconclusive evidence, that they were the main causes of the wide interest rate spread. In fact, the spread is closely linked to institutional/structural factors such as non-competitiveness in the banking sector, imprudent lending practices and poor and/or inadequate banking supervision. Policies for improving the institutional infrastructure and thus moderating the spreads are highlighted.
Keywords: Finance -- Kenya; Banks and banking -- Kenya; Economics -- Kenya; Interest rates -- Kenya; Economic development -- Kenya